2006
DOI: 10.22260/isarc2006/0159
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Model of External Resource Allocation for Resource-Constrained Project Scheduling Problems

Abstract: Construction project scheduling is crucial to project success. From the perspective of contractors, a practical schedule based on engineering experience not only improves the accuracy of project duration and cost estimation during the bidding process, but also facilitates the operation during project execution. This study employs Constraint Programming (CP) techniques to resolve resource-constrained project scheduling issues. A new scheduling model aiming for the minimization of total project cost, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[9][10][11] To better understand OM, the cost of production (CoP) has become an escalating problem in manufacturing. According to Shih and Liu, 12 CoP includes manufacturing labor costs, overhead costs and material costs that are needed for production. CoP increases when the total quantity of production increases.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] To better understand OM, the cost of production (CoP) has become an escalating problem in manufacturing. According to Shih and Liu, 12 CoP includes manufacturing labor costs, overhead costs and material costs that are needed for production. CoP increases when the total quantity of production increases.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Although in a scheduling problem in PPC, idle cost relating to labor, along with other costs, was considered in a new scheduling model to minimize the total CoP. 12 However, they further concluded that activity cost should be based on value-added resources related to the cost of labor, cost of materials and other related costs. Following Eiliat, 19 an empirical study on the total operational cost model was developed for a single product manufacturing system.…”
Section: Background and Literature Reviewmentioning
confidence: 99%